Social skills - Collins, Lorraine (Boston, MA : Allyn & Bacon Professional, 2002)
In this tape, Dr. Lorraine Collins teaches a group of participants how to listen, how to ask for feedback, how to give and receive approriate criticism, and how to ask for support from other people
Moderator: Jon Carlson, Judy Lewis
Keywords: Small groups; Social interaction; Social skills